Analisis Pengaruh Asupan Makanan Bergizi Terhadap Konsumsi Energi Dan Produktivitas Tenaga Kerja - Sumaningsih, Rosita Ratih; , Ir. Muchlison Anis, MT (2016)
Tofus were one of nutritional food, cheap and have many consumers. Factory know Al Azhar Caring Ummah (APU) is one factory producing tofu in bulk. In one day factory will produce 500-600 kg of soybeans into tofu. The high request of tofu demands corporation to fulfill these request. Factory know Al Azhar Caring Ummah (APU) is one factory producing tofu in bulk. In one day factory will produce 500-600 kg of soybeans into tofu There were 5 operators working to fulfill the request. The high of request didn't balance with the labors. The five operators have to put all the power and ability out to fulfill the request. While working the operator often complaining exhaustion. One of the ways to decrease exhaustion was giving nutritional food. A caloric need determined by counting uses Basal Metabolic Rate (BMR). Caloric needs each operator as follows Mr. Handoko 1697,41 calorie, Mr. Ali 2348,92 calorie, Mr. Ulum 1925,14 calorie, Mr. Yudi 1872,92 calorie, and Mr. Sugeng 1934, 92 calorie. There were 3 trials did in this study. To know whether the trial has an influence or not, it conducted anova test and to know what the trial which has more significant influence, it conducted tukey HSD test. The most significant take effect trial was treatment I. Giving nutritional food could decrease the value of energy consumption and increase labor productivity. Treatment I could decrease the value of energy consumption each labor Mr. Handoko from 4,83 to 4,114; Mr. Ali from 5,506 to 4,194; Mr. Ulum from 5,704 to 4,434; Mr. Yudi from 5,32 to 4,691; and Mr. Sugeng from 4,412 to 4,005. Moreover, nutrious food intake at the treatment I also could increase productivity each labor, Mr. Handoko 12,367%, Mr. Ali 9,09%, Mr. Ulum 12,354%, Mr. Yudi 5,079% and Mr. Sugeng 9,783 % Keywords: Demand, BMR, Energy Consumption, Productivity